Penegakan Hukum Di Zona Ekonomi Eksklusif Indonesia (Zeei) Dalam Rangka Kepentingan Nasional Indonesia Di Bidang Kelautan - Bambang S. Irianto (Jurnal Justiciabelen, 2022)
This research is classified as normative legal research. The approach used is the statute approach, legal principles, legal theories, legal concepts. The juridical approach in this research is a problem approach based on the applicable laws and regulations, while the normative approach is a problem approach that examines the law in law so that conclusions can be drawn that are logical, coherent and systematic. Case Approach with the case approach is done by examining cases related to the issue at hand, and has become a decision that has permanent legal force.The results of the study show that there is still inconsistency in law enforcement in the EEZ for fishery potential by the Indonesian Navy in the Exclusive Economic Zone (EEZ), Indonesia is based on the United Nations convention regarding the Law of the Sea in 1982 with Law Number 17 of 1985 concerning legalization. on the United Nations Convention on the Law of the Sea (UNCLOS) and Law Number 45 of 2009 concerning Fisheries. Illegal fishing still occurs in the Indonesian Exclusive Economic Zone by foreign vessels, which is caused by weak patrols in the ZEEI area and is supported by the opening of the ZEEI area, the patrol vessels are less modern to compete with foreign fishing vessels, and the fish resources that are in the ZEEI have not been exploited by Indonesian fishermen according to Law No. 45 of 2009 concerning Fisheries is carried out by legal proceedings and is tried in court, and is sentenced to a sentence which is usually a fine. In the event that a prison sentence is allowed.